U–Pb SHRIMP detrital zircon dating of metamorphic rocks in north–central Chile (28°–33°S): Evidence for Carboniferous and Triassic metamorphism in a subduction setting. (November 2020) - Hervé, F.; Calderón, M.; Fanning, C.M.; Pankhurst, R.J.; Navarro, J.
Abstract: U–Pb SHRIMP detrital zircon dating of ten samples of metamorphic "basement" rocks in north-central Chile and one granitic rock, improve knowledge of sedimentary, metamorphic and plutonic events in this segment of the Andean margin. The oldest possible sedimentation ages (Ordovician) come from a micaschist at Huentelauquén (477 Ma) and a granofels from a migmatite at Las Cruces (470 Ma) whose garnet-bearing granitic neosome (ca. 320 Ma) is essentially coetaneous with the extensive Coast Range Batholith. The rest of the samples show probable Carboniferous or Late Triassic maximum depositional ages. The late Paleozoic low-to-medium grade metasedimentary components of the basement, interpreted as forming part of a paleo-accretionary complex, have detrital zircon age patterns with prominent Famatinian and Grenville-age peaks; these are much less prominent in the Late Triassic rocks. The latter were deformed and metamorphosed shortly after their deposition, although some do not show visible evidence of metamorphism. Contemporaneous Triassic sedimentary, metamorphic and igneous events are recorded in Mejillones Peninsula (22°S) and in the Chonos archipelago (44°–47°S) but not in the 34°–42°S central Chile sector of the fossil accretionary complex. These events predate generalized Jurassic subduction beneath the western Gondwana continental margin that initiated the Andean orogenic cycle. Highlights: New SHRIMP U-Pb zircon dating of the sedimentary, metamorphic and plutonic events in north-central Chile segment of the Andean margin. Central Chile basement is mostly Carboniferous to late Triassic, with the Carboniferous sedimentary protoliths having Proterozoic to early Paleozoic provenance. Triassic protoliths record pre-Jurassic subduction and metamorphism. Triassic metamorphism is well established in the Norte Chico segment, but absent in the south-Central Chile segment. Reinforcing the N-S segmented nature of the accretionary margin to southwestern Gondwana.